Tipping the Scale? : The Workings of Monetary Policy through Trade - Adler, Gustavo (IMF Working Papers; Working Paper, 2017)
Monetary policy entails demand augmenting and demand diverting effects, with its impact on the trade balance-and spillovers to other countries-depending on the relative magnitude of these opposing effects. Using US data, and a sign-restricted structural VAR identification strategy, we investigate how monetary policy shocks affects the trade balance, shedding light on the importance of the two effects. Overall, the results indicate that monetary policy has a meaningful impact on the trade balance. A monetary loosening (tightening) leads to a strengthening (weakening) of the overall trade balance, indicating that, on average, demand diversion dominates. This effect of monetary policy on trade is revealed in full when distinguisging between trading partners with fixed exchange rates-for which only demand augmenting operates-and flexible exchange rates-for which both effects operate. We also explore spillover differences between conventional and unconventional monetary policy, as well as changes in spillovers in the postcrisis period (due to an impaired monetary transmission mechanism). While our results suggest that monetary policy comes with spillovers through trade, they should not be interpreted as evidence against the use of this policy instrument as such. From a global perspective, optimal monetary policy should be assessed in conjunction with deployment of other policy measures, inclluding the ability of recipient countries to deploy their own policy measures to offset undesirable spillovers.